Prevalence of Parasitic Contamination in Lettuce Vegetables Sold in Public Markets in Davao City - Jayma, Dennisse Kirsten G.; Enopia, Genelyn T.; Utida, Keen Aubrill P.; Solano, Roel Nickelson M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aims to assess parasitic contamination in lettuce (Lactuca sativa) from selected public markets in Davao City, Philippines. Using a quantitative cross-sectional design, a total of 60 samples were collected from Agdao, Bankerohan, and Toril Public Markets. Each sample was placed in sterile plastic bags and sent to the University of Mindanao Medical Technology Laboratory for examination. Using the method of Hoffman, Pons, and Janer, the samples were washed with saline, filtered, and examined using direct wet mount technique after overnight sedimentation. Four samples were positive for parasites, corresponding to a total prevalence of 6.67 percent. The parasites identified were Strongyloides stercoralis, Balantidium spp., filariform larva, and a trematode egg. It was also found that there is no significant difference in parasitic contamination among the three public markets. The presence of parasites in commonly consumed raw vegetables like lettuce poses a significant threat to consumer safety. Hence, the researchers recommend that local health agencies in the community strengthen educational initiatives targeting vendors, food handlers, consumers, and the general public on proper vegetable handling and safe preparation practices. It is recommended that further research be conducted on effective methods for washing lettuce and other vegetables before consumption to safeguard the public from possible parasitic infections and outbreaks in the future.